Brief Report: Single‐nucleotide polymorphisms in VKORC1 are risk factors for systemic lupus erythematosus in Asians. Issue 1 (27th December 2012) - Kaiser, Rachel; Taylor, Kimberly E.; Deng, Yun; Zhao, Jian; Li, Yonghong; Nititham, Joanne; Chang, Monica; Catanese, Joseph; Begovich, Ann B.; Brown, Elizabeth E.; Edberg, Jeffrey C.; McGwin, Gerald; et al.
Abstract: Objective: The increased risk of thrombosis in systemic lupus erythematosus (SLE) may be partially explained by interrelated genetic pathways for thrombosis and SLE. The present study was undertaken to investigate whether 33 established and novel single‐nucleotide polymorphisms (SNPs) in 20 genes involved in hemostasis pathways that have been associated with deep venous thrombosis (DVT) in the general population are risk factors for SLE among Asian subjects. Methods: Patients in the discovery cohort were enrolled in 1 of 2 North American SLE cohorts. Patients in the replication cohort were enrolled in 1 of 4 Asian or 2 North American cohorts. We first genotyped 263 Asian patients with SLE and 357 healthy Asian control subjects for 33 SNPs in the discovery phase, and then genotyped 5 SNPs in up to an additional 1, 496 patients and 993 controls in the replication phase. Patients were compared to controls for bivariate association with minor alleles. Principal components analysis was used to control for intra‐Asian ancestry in the replication cohort. Results: Two genetic variants in the gene VKORC1 were highly significant in both the discovery and replication cohorts: rs9934438 (in the discovery cohort, odds ratio [OR] 2.45, P = 2 × 10 −9 ; in the replication cohort, OR 1.54, P = 4 × 10 −6 ) and rs9923231 (in the discovery cohort, OR 2.40, P = 6 × 10 −9 ; in the replication cohort, OR 1.53, P = 5 × 10 −6 ). These associations were significant in the replication cohort after adjustment for intra‐Asian ancestry: for rs9934438, OR 1.34, P = 0.0029; for rs9923231, OR 1.34, P = 0.0032. Conclusion: Genetic variants in VKORC1, which are involved in vitamin K reduction and associated with DVT, correlate with SLE development in Asian subjects. These results suggest that there may be intersecting genetic pathways for the development of SLE and thrombosis.